The correlation between immunoglobulin levels with cyst count in patients with and without surgery for hydatid disease - Abd Ali, Hawraa Neama; Ali, Saba Fadhil (Journal of Neonatal Surgery, 2025)
Background: Hydatid disease remains a major public health problem in all endemic areas due to Echinococcus granulosus infection. High immunoglobulin levels determine the immune response to hydatid cysts. Knowledge about the association of immunoglobulins with cyst pathogen burden thus helps understand disease activity and develop better therapeutic strategies. Aim of study: To evaluate immunoglobulin levels (IgA, IgE, IgG) in relation to cyst number in patients with hydatid disease who underwent surgical removal of cysts and those who did not undergo surgery. Methodology: Three groups of patients participated in the case control study divided into surgically treated patients with hydatid disease, patients who did not undergo surgery and control groups. Immunoglobulin measurements were performed by ELISA while cysts was confirmed by MRI. Results: The levels of IgA along with IgE and IgG were elevated significantly in non-operated patients compared to operated patients when results were analyzed (p < 0.0001). Non-operated patents showed a strong positive link between cyst count measurements and IgA (r = 0.777, p < 0.0001) as well as IgE (r = 0.655, p < 0.0001) and IgG (r = 0.713, p < 0.0001). Cyst count showed relationships that remained statistically significant for the operated patients although they were less strong with IgA (r = 0.391, p = 0.033) and IgE (r = 0.521, p = 0.003) and IgG (r = 0.465, p = 0.010). Conclusion: Disease severity shows a meaningful relationship between cyst number and immunoglobulin levels.